Legal analysis of determination of the status of evidence in the criminal case of corruption of TWP AD in the Supreme Court's Cassation Decision Number 407-K/MIL/2023 - Muchlis Harianto (Annals of Justice and Humanity, 2024)
Purpose: Corruption is a serious problem in various countries, including Indonesia. Determination of the status of evidence in corruption cases has great significance for all parties involved. The corruption case of TWP AD at the cassation level stipulates that certain evidence is confiscated for the state. While at the first level and appeal level decisions, the evidence is confiscated for the state C.q. TWP AD. Research Methodology: This study uses a normative legal research type, namely legal research conducted by examining library materials or secondary data through library research. Results: Changes in the determination of the status of evidence at the cassation level are based on Article 18 paragraph (1) letter a in conjunction with Article 38 B paragraph (2) of the Corruption Eradication Law without considering the provisions of Article 19 paragraph (1) and the real impact on the recovery of losses experienced by the Indonesian Army. The evidence should be returned to the rightful party, in this case the Indonesian Army through TWP AD considering that the source of funds for TWP AD comes from deductions from the salaries of Soldiers and Civil Servants in the Indonesian Army environment every month. In addition, additional criminal penalties in the form of replacement money should also be deposited to the state C.q. TWP AD, because both the evidence and the replacement money are the result of corruption. Minister of Finance Regulation No. 145 / PMK.06 / 2021 regulates that the parties authorized to submit proposals for the management of confiscated state goods to the Minister of Finance are the Prosecutor's Office, the Corruption Eradication Committee, and the Auditorate. Bureaucratic procedures and processes are obstacles to the effective implementation of the Minister of Finance Regulation.